2020
DOI: 10.3329/ptcb.v30i2.50694
|View full text |Cite
|
Sign up to set email alerts
|

Plant Regeneration from Protocorm Like Body (PLB) derived Callus of Dendrobium barbatulum Lindl.

Abstract: In vitro regenerative potential of protocorm like bodies (PLBs) of Dendrobium barbatulum were assessed. The formation of secondary PLBs from the primary PLBs that formed from the callus, it is derived from a few larger injured protocorm like bodies. The injured larger PLBs were cultured on half strength MS supplemented with different concentrations of BAP (0.32, 1.62, 3.23 and 16.15 μM), Zn (0.46, 2.28, 4.56 and 22.80 μM) and Kn (0.47, 2.33, 4.65 and 23.25 μM). The highest percentage of secondary PLBs (66.33%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Pale green color callus was developed from TDZ hormone with less frequency compared to BAP-induced callus. Similarly, BAP and TDZ proved to be suitable for callus induction and PLB regeneration in D. chrysotoxum (Roy et al 2003) and BAP alone in D. barbatulum (Pyati 2020).…”
Section: Effect Of Cytokinin On Callus Inductionmentioning
confidence: 99%
“…Pale green color callus was developed from TDZ hormone with less frequency compared to BAP-induced callus. Similarly, BAP and TDZ proved to be suitable for callus induction and PLB regeneration in D. chrysotoxum (Roy et al 2003) and BAP alone in D. barbatulum (Pyati 2020).…”
Section: Effect Of Cytokinin On Callus Inductionmentioning
confidence: 99%
“…In another study, culturing the PLB of Aerides crispum Lindl. on ½ MS medium supplemented with BA (1.0 mg L −1 ) + NAA (0.5 mg L −1 ) stimulated the highest percentage of PLB formation (84.3%) (Pyati, 2022). These findings confirmed that orchid species vary in the percentage of PLB formed, as well as, the plant growth regulators (PGRs) needed, and the BA:IBA (mg L -1 ) BA+IBA (mg L -1 ) results were consistent with the results of other studies, where the protocorms of orchid species such as Cypripedium subtropicum S.C.Chen & K.Y.Lang, and Paphiopedilum Alma Gavaert showed low survival rates, which was attributed to vitrification, followed by the browning of tissues, and subsequently, explant death (Hong, Chen, & Chang, 2008;Perner et al, 2022).…”
Section: Plantlet Regenerationmentioning
confidence: 99%